The Renewable Energy: Environmentally Friendly Algae Biofuel - Bhalerao, Nikhilesh; Metkar, Sangeeta (Three E Science Institute, 2020)
Due to the limited availability of fossil fuels and the continuous increase in world energy demand, it will lead to an energy crisis in the future. The use of these energetic resources is responsible for the accumulation of greenhouse gases in the atmosphere that is associated with several adverse effects on the environment. Therefore, it is worth to search for different energy supplies that are renewable and environmentally friendly energy fuel. The alternative fuel is biodiesel, and its primary sources are oil seeds, used cooking oil, algae. Among which microalgae are photosynthetic microorganisms that can achieve high oil contents. This oil is suitable for producing biodiesel; thus, microalgae are considered a promising sustainable energetic resource that can reduce the dependence of fossil fuel. Biodiesel production from microalgae includes several steps, such as cell cultivation and harvesting, oil extraction, and biodiesel synthesis. Biodiesel is usually used by blending with Petro diesel, but it can also use in pure form. Biodiesel is a sustainable fuel, as it can be produced throughout the year and can run an engine with certain modifications. It can satisfy the needs and can also meet the demands of the future generation to come.